2020
DOI: 10.1159/000510356
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Capecitabine Alone or in Combination in Advanced Metastatic Breast Cancer Patients Previously Treated with Anthracycline and Taxane: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> Capecitabine is frequently used alone or combined with other chemotherapy agents for the treatment of metastatic breast cancer in relapsed patients. <b><i>Objective:</i></b> The objective of this meta-analysis is to evaluate the effectiveness and safety of capecitabine monotherapy versus combination in the treatment of metastatic breast cancer patients pretreated with anthracycline and taxane. <b><i>Methods:</i></b&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Factors that could account for this observation have been identified. Capecitabine toxicity profiles differ in monotherapy and combination regimens; in particular, combination therapy might be expected to be associated with higher levels of adverse events [59]. However, serious adverse effects such as nausea, HFS, mucositis, and abdominal pain, which often prompt treatment discontinuation, are more prevalent in monotherapy schedules [6,59].…”
Section: Discussionmentioning
confidence: 99%
“…Factors that could account for this observation have been identified. Capecitabine toxicity profiles differ in monotherapy and combination regimens; in particular, combination therapy might be expected to be associated with higher levels of adverse events [59]. However, serious adverse effects such as nausea, HFS, mucositis, and abdominal pain, which often prompt treatment discontinuation, are more prevalent in monotherapy schedules [6,59].…”
Section: Discussionmentioning
confidence: 99%
“… 11 13 In pretreated MBC patients capecitabine has been investigated with dosages between 825 mg/m 2 BID and 1250 mg/m 2 BID in combination with other cytotoxic drugs. 20 It has been demonstrated that the capecitabine dosage can be reduced, either in mono or in combination therapy, to minimise adverse events without compromising efficacy in terms of TTP or overall survival (OS). Results of retrospective analyses support a starting dose of capecitabine 1000 mg/m 2 BID.…”
Section: Methodsmentioning
confidence: 99%
“…do not demonstrate an increase in overall survival (OS). [2][3][4] Anthracyclines and taxanes are the mainstay chemotherapy agents for breast cancer, but many patients with metastatic breast cancer have already received these agents in the early course of disease. They cannot use them further due to drug resistance or cumulative toxicities.…”
Section: A Prospective Open-label Multicenter Phase IV Clinical Trial...mentioning
confidence: 99%
“…In the treatment of metastatic breast cancer, monotherapy is usually preferred due to a lower impact on the quality of life of patients while the combination therapy do not demonstrate an increase in overall survival (OS). 2 4 Anthracyclines and taxanes are the mainstay chemotherapy agents for breast cancer, but many patients with metastatic breast cancer have already received these agents in the early course of disease. They cannot use them further due to drug resistance or cumulative toxicities.…”
Section: Introductionmentioning
confidence: 99%